Mucus degradation by pepsin: comparison of mucolytic activity of human pepsin 1 and pepsin 3: implications in peptic ulceration. Issue 3 (March 1986) - Pearson, J P; Ward, R; Allen, A; Roberts, N B; Taylor, W H
Abstract : The ability to digest mucus, mucolytic activity of isolated pepsins and samples of human gastric juice has been assayed by measuring the fall in viscosity when incubated with purified pig gastric mucus glycoprotein. Pure human pepsin 1, the peptic ulcer associated pepsin, digested gastric mucus glycoprotein at a faster rate than did pure human pepsin 3 (the principal human pepsin), or the equivalent pig pepsin (pepsin A). At pH 2.0 pepsin 1 had twice the mucolytic activity of pepsin 3. Above pH 3.8 this difference became more marked and whereas pepsin 1 caused substantial mucolysis up to and including pH 5.1, pepsin 3 had minimal activity. At pH 4.0 pepsin 1 had six times the mucolytic activity of pepsin 3. Gastric juices from patients with duodenal ulcer each exhibited substantial mucolytic activity between pH 2 to 5, similar to that of pepsin 1. In contrast, gastric juice from non-symptomatic volunteers exhibited little mucolytic activity above pH 4. Analysis of the mucus glycoprotein by gel filtration showed that an increase in lower molecular weight, pepsin degraded, glycoprotein was associated with the fall in mucus viscosity for all enzyme preparations. These results showed that pepsin 1 can digest the mucus more effectively than pepsin 3 and at higher pH values. The raised concentrations of pepsin 1 in the juice of peptic ulcer patients may thus promote the ulcerative process by increased erosion of the mucus barrier under conditions likely to pertain in the duodenal bulb as well as the stomach.